DO STATUS-SEEKING MOTIVES ENHANCE ECONOMIC GROWTH? A SMALL OPEN GROWTH MODEL. (18th August 2016) - Chang, Juin-Jen; Wang, Wei-Neng; Chen, Ying-An
Abstract : This paper explores the growth effects of both consumption- and wealth-induced social comparisons in a unified small open endogenous growth model. We analytically show that in an open economy not only do these two distinct status-seeking motives have very different growth effects, but these growth effects are also quite different from the conventional wisdom based on a closed economy. Status-seeking behavior need not favor economic growth. The asset portfolios of households and the imperfection of the international asset market both play an important role and jointly govern the growth effects of social status seeking. We also perform a quantitative experiment, showing that our analytical findings are robust and empirically plausible. Our analysis provides novel implications for social comparisons and new insights into the literature.